The Effect of Traditional Games on the Improvement of Gross Motor Skills Among Seventh Grade Students at PAB 8 Junior High School Sampali - Limbong, Irvan; Helmi, Boby (Journal of Physical Education Innovation, 2025)
This study empirically investigates the effect of traditional games specifically Bentengan and Gobak Sodor on the improvement of gross motor skills among seventh-grade students at PAB 8 Junior High School Sampali in the 2023/2024 academic year. Employing a quasi-experimental design with a one-group pre-test and post-test model, the research involved 12 student participants. Data were collected using tests of arm power (medicine ball throw), running speed (20-meter sprint), and agility (4×5 meter shuttle run). Statistical analysis was conducted using a paired-sample t-test to determine the significance of the differences between pre-test and post-test results. The findings indicated significant improvements in all measured aspects of gross motor ability: arm power increased from 1.76 to 2.08, running speed improved from 6.16 seconds to 5.96 seconds, and agility improved from 16.52 seconds to 15.41 seconds. The t-test results showed that tcount > ttable for all variables, confirming a statistically significant effect. The study concludes that traditional games have a positive and significant impact on enhancing students’ gross motor skills, suggesting their potential integration into physical education programs as an effective, culturally rooted pedagogical tool.